2014
DOI: 10.1007/s12311-014-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Affective Disturbances Following Focal Brainstem Lesions: A Review and Report of Three Cases

Abstract: Although insights in cerebellar neurocognition and affect are continuously growing, little is known about the role of the brainstem in cognitive and behavioural processing. In this paper, it is hypothesized that the brainstem is an inherent functional part of the cerebellocerebral network subserving cognition and affect, and that isolated brainstem damage may cause a constellation of symptoms closely resembling the cerebellar cognitive affective syndrome (CCAS) following cerebellar pathology. In order to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 53 publications
1
32
0
6
Order By: Relevance
“…Three patients (TH6, 11,14) were available for follow-up NIRS data. NIRS was performed three times for TH6, and two times for TH11 and TH14, respectively.…”
Section: Follow-up Nirs Testsmentioning
confidence: 99%
“…Three patients (TH6, 11,14) were available for follow-up NIRS data. NIRS was performed three times for TH6, and two times for TH11 and TH14, respectively.…”
Section: Follow-up Nirs Testsmentioning
confidence: 99%
“…A 2-year longitudinal study investigating the brainstem volume showed an atypical development in children and adolescents with ASD compared to matched controls, characterized by an increase of GM brainstem volume over time (Jou et al, 2013). Moreover, recent lesion studies suggested an involvement of the brainstem in neurocognition (D'Aes et al, 2015), and specifically a cognitive dysfunction after brainstem damage (Fu et al, 2017): thus, it is crucial to analyze the impact of IQ level on brainstem volume. Moreover, recent lesion studies suggested an involvement of the brainstem in neurocognition (D'Aes et al, 2015), and specifically a cognitive dysfunction after brainstem damage (Fu et al, 2017): thus, it is crucial to analyze the impact of IQ level on brainstem volume.…”
Section: Introductionmentioning
confidence: 99%
“…Further, both quantitative and qualitative sex differences have been detected in the neuroanatomy of children (Retico et al, 2016) and adults (Ecker et al, 2017) with ASD, and the brainstem is part of such sexually dimorphic brain regions (Lai et al, 2013). Moreover, recent lesion studies suggested an involvement of the brainstem in neurocognition (D'Aes et al, 2015), and specifically a cognitive dysfunction after brainstem damage (Fu et al, 2017): thus, it is crucial to analyze the impact of IQ level on brainstem volume. None of the previous studies on brainstem structural MRI in ASD individuals has addressed this issue, and more broadly low-functioning children have been neglected in neuroanatomical autism research (Jack & Pelphrey, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment caused by pathological changes in the brain stem has been gaining attention recently. D'aes and Mariën [ 8 ] reviewed 75 patients who had experienced brain stem stroke and also examined 3 additional patients and reported that affected cognitive functions such as decline in general intellectual capacity, attention, executive functions, memory, visuospatial skills, language, and praxis were observed. Hoffmann and Watts [ 9 ] reported that cognitive impairment was found in the acute phase of brain stem stroke, along with a reduction of blood flow to the frontal and parietal lobes.…”
Section: Discussionmentioning
confidence: 99%